PEG-Lipid-PLGA Hybrid Particles for Targeted Delivery of Anti-Inflammatory Drugs - Jana Ismail; Lea C. Klepsch; Philipp Dahlke; Ekaterina Tsarenko; Antje Vollrath; David Pretzel; Paul M. Jordan; Kourosh Rezaei; Justyna A. Czaplewska; Steffi Stumpf; Baerbel Beringer-Siemers; Ivo Nischang; et al. (MDPI AG, 2024)
Hybrid nanoparticles (HNPs) were designed by combining a PLGA core with a lipid shell that incorporated PEG-Lipid conjugates with various functionalities (-RGD, -cRGD, -NH2, and -COOH) to create targeted drug delivery systems. Loaded with a neutral lipid orange dye, the HNPs were extensively characterized using various techniques and investigated for their uptake in human monocyte-derived macrophages (MDMs) using FC and CLSM. Moreover, the best-performing HNPs (i.e., HNP-COOH and HNP-RGD as well as HNP-RGD/COOH mixed) were loaded with the anti-inflammatory drug BRP-201 and prepared in two size ranges (dH ~140 nm and dH ~250 nm). The HNPs were examined further for their stability, degradation, MDM uptake, and drug delivery efficiency by studying the inhibition of 5-lipoxygenase (5-LOX) product formation, whereby HNP-COOH and HNP-RGD both exhibited superior uptake, and the HNP-COOH/RGD (2:1) displayed the highest inhibition.